SCHOOL COMMITTEE PARTICIPATION IN REALIZING THE QUALITY OF EDUCATION - Kusumawati, Erna (Sean Institute, 2022)
The study aims to describe the participation of school committees in improving the quality of schools. Researchers applied the research procedure to describe the participation of school committees. Research informants are the head of the school committee, the principal, committee members, teachers, parents, the community and school stakeholders. Data were collected through interviews, observations and documentation studies. Data analysis techniques include the following processes: data collection, data reduction, data presentation, and drawing conclusions. Checking the validity of the data is carried out through a triangulation test. The results of the study found that the role of school committees is effective in improving the quality of education. The role of the school committee includes coordinating, providing advice or input, providing aspirations, conducting supervision, checking school development from allocated funds, providing moral and material support as well as the mind. The role of the school committee has contributed to the fields of student affairs, curriculum, public relations of school facilities and infrastructure as well as strengthening school management.